Shielding Young Minds: Mukhalatah as a Prophetic Strategy to Prevent Speech Delay in the Screen Time Era - Adhim Rajasyah; Muhajirin Muhajirin (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2025)
This study explores the adverse effects of excessive screen time on speech delay among early childhood in Indonesia. It proposes the Mukhālaṭah concept as a preventive solution rooted in Prophetic hadiths. Employing a qualitative literature-based approach with a ma‘anil hadith methodology, the research analyzes primary sources, such as Fathul Bari by Ibn Hajar al-Asqalani, and secondary materials, including journals and books on child development. Findings reveal that high screen time, averaging 5.7 hours daily among Indonesian children aged 0-6, significantly hinders language acquisition by reducing verbal interactions essential for cognitive and emotional growth, leading to speech delays affecting 5-10% of young children. Mukhālaṭah, derived from hadiths in Sahih Bukhari (indices 6129 and 6203) emphasizing interactive mingling and affectionate communication, promotes active parental engagement through play, empathy, and dialogue to stimulate language skills. The study introduces the SHIELD strategy (Serve, Hear, Interact, Engage, Limit, Develop) as a framework for implementing strategies to limit gadget exposure, foster responsive interactions, and create stimulating environments. Ultimately, this integrative Islamic approach empowers parents to counteract digital disruptions, ensuring holistic child development while aligning traditional values with modern challenges.